Aboveground herbivory does not affect mycorrhiza-dependent nitrogen acquisition from soil but inhibits mycorrhizal network-mediated nitrogen interplant transfer in maize - He, Chenling; Lin, Yibin; Zhang, Yifang; Tong, Lu; Ding, Yuanxing; Yao, Min; Liu, Qian; Zeng, Rensen; Chen, Dongmei; Song, Yuanyuan (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) are considered biofertilizers for sustainable agriculture due to their ability to facilitate plant uptake of important mineral elements, such as nitrogen (N). However, plant mycorrhiza-dependent N uptake and interplant transfer may be highly context-dependent, and whether it is affected by aboveground herbivory remains largely unknown. Here, we used 15N labeling and tracking to examine the effect of aboveground insect herbivory by Spodoptera frugiperda on mycorrhiza-dependent N uptake in maize (Zea mays L.). To minimize consumption differences and 15N loss due to insect chewing, insect herbivory was simulated by mechanical wounding and oral secretion of S. frugiperda larvae. Inoculation with Rhizophagus irregularis (Rir) significantly improved maize growth, and N/P uptake. The 15N labeling experiment showed that maize plants absorbed N from soils via the extraradical mycelium of mycorrhizal fungi and from neighboring plants transferred by common mycorrhizal networks (CMNs). Simulated aboveground leaf herbivory did not affect mycorrhiza-mediated N acquisition from soil. However, CMN-mediated N transfer from neighboring plants was blocked by leaf simulated herbivory. Our findings suggest that aboveground herbivory inhibits CMN-mediated N transfer between plants but does not affect N acquisition from soil solutions via extraradical mycorrhizal mycelium.